Spontaneous Loss of Tolerance of Autoreactive B Cells in Act1 -Deficient Rheumatoid Factor Transgenic Mice - Giltiay, Natalia V; Lu, Yi; Cullen, Jaime L; Jørgensen, Trine N; Shlomchik, Mark J; Li, Xiaoxia (The Journal of immunology (1950), 2013)
Self-reactive B cells in BALB/c AM14 transgenic (Tg) rheumatoid factor mice are not subject to central or peripheral tolerization. Instead, they remain at a stage of “clonal ignorance”; that is, they do not proliferate and differentiate into Ab-forming cells. However, the immunoregulatory mechanisms that prevent autoantibody production in these mice remain unclear. In this study, we show that crossing AM14 Tg mice to a mouse strain deficient in Act1, a molecule involved in the regulation of BAFF-R and CD40-signaling in B cells, results in spontaneous activation of AM14 Tg B cells and production of AM14-specific Abs. Three- to 5-mo-old AM14 Tg Act1−/− mice showed significant expansion of AM14 Tg B cells, including a 2- to 3-fold increase in the spleen and cervical lymph nodes compared with AM14 Tg Act1+/+ mice. Furthermore, in the presence of endogenous self-Ag (IgHa congenic background), AM14 Tg Act1−/− B cells were spontaneously activated and differentiated into Ab-forming cells. In contrast with previous studies using AM14 Tg MLR.Faslpr mice, we found that a significant number of AM14 Tg cells AM14 Tg Act1−/− mice displayed phenotypic characteristics of germinal center B cells. Anti-CD40L treatment significantly limited the expansion and activation of AM14 Tg Act1−/− B cells, suggesting that CD40L-mediated signals are required for the retention of these cells. Our results support the important role of Act1 in the regulation of self-reactive B cells and reveal how Act1 functions to prevent the production of autoantibodies.